Fluorescent Calcium Nanocluster-Driven Theranostic Nanoplatforms for Advanced Imaging and Therapy in Breast Tumor - Mehata A.K.; Verma V.K.; Singh V.; Setia A.; Vikas N.; Viswanadh M.K.; Sabbarwal S.; Kumar M.; Koch B.; Muthu M.S. (My University, 2025)
Biocompatible CaCO3 nanoclusters were prepared by using a simple biomineralization technique. Employing CaCO3 nanoclusters in breast cancer treatment provides an exciting avenue for theranostics, which merges precise imaging with individualized treatment plans. They were highly suitable for improving the efficacy and precision of breast cancer detection and therapy with minimal adverse effects due to their biocompatibility, controlled drug release, pH sensitivity, and adaptability. In our current study, we proposed a palbociclib (PBB)-loaded fluorescent calcium nanocluster-based redox-sensitive drug delivery system for efficient breast cancer imaging and therapy. The developed nanoparticles were analyzed for their morphology and various physicochemical properties. The particle sizes of the formulated FNC-PBB-CS-NPs (nonredox-sensitive) and FNC-PBB-CS-SS-NPs (redox-sensitive) nanoparticles were 150.2 ± 2.1 and 160.4 ± 1.4 nm, respectively. The zeta potential of nonredox-sensitive nanoparticles was measured to be +17.12 ± 1.34 mV, while the zeta potential of redox-sensitive nanoparticles was +14.32 ± 1.17 mV. The entrapment efficiencies of FNC-PBB-CS-NPs and FNC-PBB-CS-SS-NPs were determined to be 88.74 ± 2.34 and 89.26 ± 1.21%, respectively. FNC-PBB-CS-SS-NPs demonstrated quicker drug release at acidic pH compared to FNC-PBB-CS-NPs. The cytotoxicity assay conducted on MCF-7 and T-47D cells indicated that FNC-PBB-CS-NPs and FNC-PBB-CS-SS-NPs exhibited greater cytotoxicities than free PBB. Furthermore, the Hoechst/PI dual-staining experiment demonstrated the superior activity of FNC-PBB-CS-SS-NPs over FNC-PBB-CS-NPs and free PBB. Ultrasound/photoacoustic imaging revealed that FNC-PBB-CS-SS-NPs effectively reduced tumor size, hypoxic tumor regions, and tumor vascularity compared to FNC-PBB-CS-NPs and free PBB. Additionally, in vivo optical imaging showed that the FNC-PBB-CS-SS-NPs accumulated more specifically in tumors than the other formulations. © 2025 American Chemical Society.